Orthodontic management of non-syndromic multiple supernumerary teeth - Vijay Singhvi; Supriya Nambiar; Siddarth Shetty (Wolters Kluwer Medknow Publications, 2013)
Hyperdontia amounts to an odontostomatologic anomaly wherein, there is an increase in tooth number irrespective of the location. This case report represents a form of hyperdontia characterized by bilateral multiple supernumerary teeth in both the jaws without any evident familial history.